2015
DOI: 10.1080/19317611.2014.959631
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Forced Sex and Subsequent Sexual, Drug, and Mental Health Outcomes: African American and Hispanic Women in the Southeastern United States

Abstract: Objectives This cross-sectional study examined African American and Hispanic women’s (N = 1,509) self-reports of unwanted forced sex and its association with behavioral and mental health outcomes after the event. Methods Twenty percent of the women had experienced forced sex (1st occurrence at age 15 years or younger for 10%, 1st occurrence at older than 15 years of age for 10%). Results Regardless of when forced sex 1st occurred, women were more likely to have engaged in unprotected vaginal and anal sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…and asthma. Previous research has also established a relationship between a history of rape and other SV victimization and having sexually transmitted diseases (STDs) (Brookmeyer et al, 2017;Jones et al, 2015;Sarkar, 2010;Williams et al, 2013). For example, Brookmeyer and colleagues (2017) found that women who experienced forced sex were more likely than women who did not to be diagnosed with chlamydia, herpes, and genital warts.…”
Section: Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…and asthma. Previous research has also established a relationship between a history of rape and other SV victimization and having sexually transmitted diseases (STDs) (Brookmeyer et al, 2017;Jones et al, 2015;Sarkar, 2010;Williams et al, 2013). For example, Brookmeyer and colleagues (2017) found that women who experienced forced sex were more likely than women who did not to be diagnosed with chlamydia, herpes, and genital warts.…”
Section: Physical Healthmentioning
confidence: 99%
“…Numerous mental health issues have been associated with prior SV victimization. For example, prior rape or other SV victimization was associated with depression (Brabant et al, 2014;Choudhary et al, 2012;Kendler & Aggen, 2014;McDougall et al, 2019;Santaularia et al, 2014;Zinzow et al, 2012;, post-traumatic stress disorder (PTSD) symptoms (Basile et al, 2015;Basile, Smith, et al, 2016b;Brabant et al, 2014;Choudhary et al, 2012;Iverson et al, 2013;Zinzow et al, 2012;, distress (Jones et al, 2015), anxiety (Choudhary et al, 2012;Iverson et al, 2013;Santaularia et al, 2014), fear (Amstadter & Vernon, 2008), and suicidal ideation (Brabant et al, 2014;Santaularia et al, 2014;Sarkar, 2010) and attempts (Iverson et al, 2013). While some of these impacts, like fear, can be immediate or happen during the violent incident(s), many of these mental health issues can be lifelong problems for SV survivors.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found higher rates of rape victimization for African-American and multiracial women compared to Caucasians and higher rates of non-rape SV victimization among multiracial and African-American men compared to Caucasians (Breiding et al, 2014). Some researchers have also reported that women with less education may be more likely than those with more education to experience forced sex during adolescence, while others report no significant differences (Decker et al, 2014; Jones et al, 2015). Black et al (2011) report that more women than men are victims of SV, but differences in prevalence vary by type of violence.…”
Section: Introductionmentioning
confidence: 99%
“…SV victimization increases risk for mental health problems (e.g., depression, anxiety) and physical health risks (e.g., sexually transmitted infections, injury; Choudhary, Smith, & Bossarte, 2012; Coker et al, 2002). SV victimization also increases risk of future violence, sexual risk behaviors, and substance use disorders (Jones et al, 2015). More than 25% of women and 11% of men will experience some form of unwanted sexual contact in their lifetime (Breiding et al, 2014).…”
mentioning
confidence: 99%